The Impact of Demographic and Economic Change on the Australian Generational Economy: Financial Sustainability, Intergenerational Inequality, and Material Living Standards - Rice, James Mahmud; Wilson, Tom; Temple, Jeromey B.; McDonald, Peter (Frontiers in Public Health, 2022)
The generational economy – which is that aspect of the economy that pertains to the economic activities of, and the economic relationships between, different ages and generations – can be evaluated on the basis of a number of different criteria. The most critical of these include the financial sustainability of the generational economy, the intergenerational inequality that the generational economy creates, and the material living standards associated with the generational. How the generational economy performs against these three criteria is, moreover, shaped by underlying processes of demographic and economic change. This paper examines how the Australian generational economy can be expected to perform in the coming decades in terms of financial sustainability, intergenerational inequality, and material living standards. Performance is evaluated under a variety of demographic and economic scenarios delineated on the basis of projected changes in fertility, mortality, overseas migration, and labour-income growth.